Nutritional perspectives of early Muslims’ eating habits - Ahmed, Idris Adewale; Asiyanbi-Hammed, Tawakalit Tope; Idris, Munirat Abolore; Mikail, Maryam Abimbola; Hammed, A.; Hammed, Ademola Monsur (Faculty of Food Science & Technology, Universiti Putra Malaysia (UPM), 2017)
In recent time, there has been a great influx of numerous processed foods into the market. The utilization of improved technologies in food ecosphere has not only led to the emergence of complex foods but has also raised concerns about their nutritional, safety and halal status among consumers. Consumers are confused whether to reject or adopt the proceesed foods and have become divided into various groups based on their eating habits. In order to ameliorate their concerns, consumers seek the adoption of knowledge-based eating habits. This review provides details on the nutritional perspectives of eating habits by early Muslims. Islam, as a complete way of life, entails well-defined eating habits as a comprehensive guide for mankind.